(untitled) - Walton, Richard (Cambridge, UK, 2000)
Initiative is a general English course which meets the needs of more advanced learners. With its main focus on reading and writing, this course emphasises vocabulary work and grammar exercises in order to ensure success in written assignments
Keywords: English language; Study and teaching,Foreign speakers,Audio-visual aids